Les États-Unis, l’Europe et la Libye : de la réhabilitation de Kadhafi à son renversement - Yahia Zoubir (L’Année du Maghreb)
For decades, relations between the West, particularly the United States, and the Jamahiriya were hostile. Muammar Gaddafi’s actions abroad prompted retaliation from the United States, who bombed Libya in 1986. The 1988 bombing of a Pan Am flight over Lockerbie, for which Libya was blamed, resulted in severe sanctions. However, from 1999 until the fall of his regime and his murder in October 2011, Gaddafi was able to normalize relations with Europe and, later, with the United States without engaging in fundamental changes in his domestic policy. This rehabilitation has left his authoritarian system intact. This article shows how Gaddafi managed to pursue a policy based opportunistic pragmatism which allowed him to survive and prolong the existence of his regime until 2011.